DAMPAK KERJASAMA SISTER CITY KOTA DKI JAKARTA DENGAN KOTA BERLIN PADA TAHUN 2016-2019 - Hakim, Aulia Rahman; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research describes the impacts of sister city cooperation between the City of DKI Jakarta and the City of Berlin, especially the impacts that occurred in 2016-2019, these impacts are related to areas of agreement that have been agreed in the MoU which contains cooperation in the field of Urban Planning, Transportation. General City, Drinking Water and Wastewater Treatment, Housing Development Planning, Economy and Culture. Jakarta's sister city cooperation with Berlin has been established for 25 years, during which time there have also been many activities carried out related to agreed fields for the advancement of the two cities. In this research, the resulting impacts focus on the city of DKI Jakarta as a city that absorbs more knowledge and direct or indirect assistance provided by the City Government of Berlin.             This research uses the theory of international cooperation to see the form of cooperation between Jakarta and Berlin in the form of a sister city. Then this research uses a pluralism perspective, supported by nation-state level analysis and uses the theory of cooperation measurement indicators.            The impacts that have resulted from the collaboration between Jakarta and Berlin are in the form of input or second opinion related to the development of each agreed area. The activities carried out in each field are in the form of workshops, exhibitions, expert visits from Berlin, placement of experts from Belrin, but from these 6 fields there is one field that does not work, namely in the field of Wastewater Treatment because there are already collaborations with other cities. Overall the cooperation carried out by the two cities runs effectively because most of these fields have been carried out activities that are used for the progress of the city, especially the City of Jakarta.Keywords: Sister City, Impact, Jakarta, Berlin, City Development, International Cooperation.